2014
DOI: 10.1504/ijode.2014.065094
|View full text |Cite
|
Sign up to set email alerts
|

The formation of political discourse within online networks: the case of the occupy movement

Abstract: How does political discourse spread in digital networks? Can we empirically test if certain conceptual frames of social movements have a correlate on their online discussion networks? Through an analysis of the Twitter data from the Occupy movement, this paper describes the formation of political discourse over time. Building on a previous set of concepts -derived from theoretical discussions about the movement and its roots -we analyse the data to observe when those concepts start to appear within the network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Occupy Wall Street (OWS): Crowd-enabled connective action network. Previous research (Conover, Ferrara, Menczer, & Flammini, 2013; Fábrega & Sajuria, 2014) has shown that this case is a prime example of this type of political activism. OWS activists showed reluctance to allow formal organizations to play a key role in the movement.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Occupy Wall Street (OWS): Crowd-enabled connective action network. Previous research (Conover, Ferrara, Menczer, & Flammini, 2013; Fábrega & Sajuria, 2014) has shown that this case is a prime example of this type of political activism. OWS activists showed reluctance to allow formal organizations to play a key role in the movement.…”
Section: Methodsmentioning
confidence: 71%
“…Previous research (Fábrega & Sajuria, 2014; has shown that this case is a prime example of this type of political activism. OWs activists showed reluctance to allow formal organizations to play a key role in the movement.…”
Section: Methodsmentioning
confidence: 75%
“…Scholars have discussed the possibility to address this problem by complementing polls with social media data (Settle et al, 2016, DiGrazia et al, 2013, Settle et al, 2016. Our study suggests that Twitter data can provide a valuable source of information for campaign decision-making, as a continuous flow of public information directly posted by individuals who express and share their opinions about politics with a wider network than just friends and family (Tumasjan et al, 2010, Fábrega and Sajuria, 2014, Barberá, 2014. This article built upon previous studies that have used social media data to measure public opinion.…”
Section: Discussionmentioning
confidence: 84%
“…Until 2017, Twitter, a microblogging site allowed for posts not longer than 140 characters and "interactions can take the form of a mention (when a user writes another username in their messages), a retweet (when a tweet from another user is replicated verbatim, usually with a "RT" at the beginning of it), or a "via" (when a user quotes the message from another user" Fábrega and Sajuria (2014). Hashtags also allow for users to follow up on conversations making it possible to see what other users (beyond a user's network) are saying about a specific issue.…”
Section: Twitter and The Bring Back Our Girls Campaignmentioning
confidence: 99%